Incidence of Intestinal Constipation During the COVID-19 Pandemic Period in Medical Students from a Private Institution in São Paulo, SP - Neto, Isaac José Felippe Corrêa; Silva, Alisson de Lucena; Tajiri, Renato Cardoso de Melo; Theis, Cláudia; Schelle, Gabriela; Pinto, Rodrigo Ambar; Nishiyama, Victor Keniti Gomes; Robles, Laercio (Journal of Coloproctology, 2023)
Introduction Chronic intestinal constipation (CIC) presents an incidence of 2.6 to 30.7% in the overall population and due to the social reality imposed by the coronavirus pandemic, some behavior changes in the Brazilian population occurred that might or not be associated with alterations of CIC prevalence.Objective To assess CIC incidence in medical students before and during the COVID-19 pandemic in Brazil in a private higher educational institution in the city of São Paulo, state of São Paulo.Methods Clinic data were collected through Google Forms software from the same students seeking to analyze the variables before (year of 2019) and during the coronavirus pandemic. The data were: age, sex, body mass index, constipation referred in a subjective way and confirmed through the ROME III criteria, feces consistency and anxiety and/or depression during the pandemic.Results A total of 126 medical students from a private higher education institution from São Paulo, SP were included. The average age was 22.9 years old, 70.6% were female and the average BMI was 23.3 kg/m2. Regarding the ROME III criteria, 32.5% presented > 2 in 2019 and 42.1% during the pandemic. Concerning the feces consistency, 31.75 and 35.71% presented dry Bristol 1 feces or in both periods, respectively.Conclusion It was observed an increase in the prevalence of chronic intestinal constipation in medical students from a private higher education institution from São Paulo, state of São Paulo, during the COVID-19 pandemic, as well as dryness in the feces.
Keywords: chronic intestinal constipation; coronavirus pandemic; medical students; ROME criteria; feces consistency